PENGARUH MODEL PEMBELAJARAAN TIPE STAD TERHADAP HASIL BELAJAR TEMATIK SISWA SEKOLAH DASAR - Lidiani Riska; Kartono Kartono; Asmayani Salimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aimed to examine how much the influence of applying STAD type cooperative model on learning outcomes in the thematic learning  of fifth grade  SDN  66 Pontianak Kota. The method used was a Non Equivalent Control Group Design experimental design. The technique of data collecting used was the measurement technique. The tool of data collecting used was a written test in the form of multiple choice. Based on the data analysis, obtained the average results of the experimental class post-test was 73.62 and the average post-test control class was 67.44. Hypothesis test results using t-test (Polled Variance) obtained tcount = 3.224 while (dk = 36 + 37-2 = 71) with a 5% significance level obtained ttable = 1.99, which means tcount >ttable, then Ha is accepted, this proved there are the effect by applying STAD type cooperative model on learning outcomes in the thematic learning of fifth grade. The calcullation results of of Es obtained = 0.52, including as medium criteria. Thus, it can be concluded that the application of the STAD type cooperative model in Thematic learning has a moderate effect on student learning outcomes of fifth grade  SDN  66 Pontianak Kota.Keywords: Influence, Learning Outcomes, STAD Type Cooperative Model, Thematic Learning.